Atomically constructing a van der Waals heterostructure of CrTe2/Bi2Te3 by molecular beam epitaxy. (15th March 2023) - Nie, Jin-Hua; Li, Rui; Miao, Mao-Peng; Fu, Ying-Shuang; Zhang, Wenhao
Abstract: A 2D heterostructure with proximity coupling of magnetism and topology can provide enthralling prospects for hosting new quantum states and exotic properties that are relevant to next-generation spintronic devices. Here, we synthesize a delicate van der Waals (vdW) heterostructure of CrTe2 /Bi2 Te3 at the atomic scale via molecular beam epitaxy. Low-temperature scanning tunneling microscopy/spectroscopy measurements are utilized to characterize the geometric and electronic properties of the CrTe2 /Bi2 Te3 heterostructure with a compressed vdW gap. Detailed structural analysis reveals complex interfacial structures with diversiform step heights and intriguing moiré patterns. The formation of the interface is ascribed to the embedded characteristics of CrTe2 and Bi2 Te3 by sharing Te atomic layer upon interfacing, showing intercoupled features of electronic structure for CrTe2 and Bi2 Te3 . Our study demonstrates a possible approach to construct artificial heterostructures with different types of ordered states, which may be of use for achieving tunable interfacial Dzyaloshinsky–Moriya interactions and tailoring the functional building blocks in low dimensions.